Integrated management of web blight of urd/mung bean by bio-seed treatment - DUBEY, S.C. (Indian Phytopathology, 2003)
Seed treatment with slurry or water mixed spores of Trichoderma viride and Glioc/adium virens gave the best protection to germinating seeds of urdlmung bean against Rhizoctonia solani. Sorghum grain based powder @ 2g kg-1seed also provided good protection and its efficacy was i~creased with application with stickers available in farm house. The rice gruel (mare) showed superiority over other stickers. Higher concentration of both antagonists T. viride and G. virens provided more protection. 106 sporesl ml/10 g seeds provided more than 60% area coverage around seeds. Integrated seed treatment with above antagonists, Rhizobium sp. and vitavax provided better protection to germinating seeds. G. virens and T. viride alone also showed superiority over fungicides. Seed treatment with G. virens/T. viride + vitavax +Rhizobium followed by G. virens/T. viride + vitavax gave maximum germination, plant vigour, number of root nodules and grain yield with minimum seedling mortality and disease intensity in both urd and mung bean. G. virens and its integrated combinations showed superiority over T. viride and its integrations.